КОМУНІКАТИВНА КУЛЬТУРА МАЙБУТНІХ ВЧИТЕЛІВ ІНОЗЕМНИХ МОВ ЯК ВАЖЛИВИЙ ПОКАЗНИК ЙОГО ПРОФЕСІОНАЛІЗМУ (Педагогіка вищої та середньої школи, 2008)
This article discloses the meaning of the term communicative culture of future teachers of foreign languages, shows its structure, components and also levels.